Melamine formaldehyde-metal organic gel interpenetrating polymer network derived intrinsic Fe-N-doped porous graphitic carbon electrocatalysts for oxygen reduction reaction - Shijina, Kottarathil; llathvalappil, Rajith; Sumitha, N. S.; Sailaja, G. S.; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchig, Takeo; Hareesh, U. S. (New Journal of Chemistry, 2018)
Fe, N doped porous graphitic carbon electrocatalyst (Fe-MOG-MF-C), obtained by pyrolysis of an Interpenetrating Polymer Network (IPN) comprised of melamine formaldehyde (MF as hard segment) and Metal-Organic Gel (MOG as soft segment), exhibited significant Oxygen Reduction Reaction (ORR) activity in alkaline medium. BET surface area analysis of Fe-MOG-MF-C showed high surface area (821 m(2) g(-1)), while TEM, Raman and XPS results confirmed Fe and N co-doping. Furthermore, a modulated porous morphology with a higher degree of surface area (950 m(2) g(-1)) has been accomplished for the system (Fe-MOG-MFN-C) when aided by a sublimable porogen, such as naphthalene. XPS results further demonstrated that these systems exhibited a better degree of distribution of graphitic N and an onset potential value of 0.91 V vs. RHE in 0.1 M KOH solution following an efficient four-electron ORR pathway. The electrocatalytic activity of Fe-MOG-MFN-C is superior to that of Fe-MOG-MF-C by virtue of its higher graphitic N content and surface area. Thus, the study presents a new class of IPN derived MF-MOG nanocomposites with the potential to generate extended versions of in situ Fe-N doped porous graphitic carbon structures with superior ORR activity.